The Influence Of Transformational Leadership On Employee Performance With Work Motivation As An Intervening Variable At PT PLN Nusantara Power Bukit Asam - Sandi, Ramona; Sutoyo; Zainuddin, Ahmad; Suminar, Lintang; Soleha, Siti Nur (PT Maju Malaqbi Makkarana, 2025)
This study analyzes the influence of transformational leadership style on employee performance and examines the role of work motivation as a mediating variable. A quantitative approach was used with path analysis based on Structural Equation Modeling–Partial Least Square (SEM-PLS). The research sample consisted of 94 employees of PT PLN Nusantara Power Bukit Asam who were selected through purposive sampling techniques. The results showed that transformational leadership style had a significant effect on employee performance (β = 0.656; T = 6,884; P = 0.000) and work motivation (β = 0.543; T = 5.429; P = 0.000). However, work motivation had no significant effect on performance (β = 0.198; T = 1,759; P = 0.079) and did not mediate the relationship between transformational leadership style and performance significantly (Z = 1.587; P = 0.112). These findings confirm that the direct influence of transformational leadership styles on employee performance is stronger than the indirect influence through work motivation.